PEMETAAN KONFLIK SOSIAL DI KOTA CILEGON PROVINSI BANTEN - Agus Sjafari (Universitas Sultan Ageng Tirtayasa, 2014)
Mapping study aims to map the social conflicts social in Cilegon. There areincluding : issues of conflict , scene , time of occurrence and actors / actors / stakeholders ,as well as the causes of conflict , chronological / events , impact , and the process ofconflict resolution . Cilegon City is a very heterogeneous population areas. It has a largeenough potential conflicts associated with the differences in value system , differentcultures , different interests . The Potential social conflicts and have a relatively high socialintensity in Cilegon City is in the field of labor and employment , land ownership disputes ,and the rejection of entertainment activities , while other potential social conflicts relatedto religious activity .